BENTUK PENYAJIAN DAN FUNGSI MUSIK RITUAL MUANG PANYAKIT PADI SUKU DAYAK KANAYATN DESA AMPANING - Kathleen Renatha Callista; Yudhistira Oscar Olendo; Asfar Muniir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research is motivated by the uniqueness of the ritual Muang Panyakit Padi which lies in the form of presentation and function of music in the ritual. Therefore researchers document the form of presentation and function of music in the ritual Muang Panyakit Padi in the form of writing and pictures. The research method used is descriptive method in the form of qualitative research and an anthropological approach. Data obtained from interviews, observations, and documentation. The data validity technique used source triangulation and observation extension. Based on data analysis, it was concluded that the ritual Muang Panyakit Padi is a ritual that aims ask to God(Jubata) for help so that the rice to be harvested is protected from all diseases. Traditionally this ritual is performed once a year before the rice harvest. This tradition is packaged in the form of a nyangahatn(prayer) that involves many groups, namely the Tuha Tahutn (the organizer), shamans, and the local community. This tradition also includes a praise event in the form of pencak silat accompanied by ensemble music. The musical ensemble consists of Dau, Agukng, and Tuma'. The function of music in the ritual Muang Panyakit Padi has a function as (1) As Accompaniment Music, (2) cultural continuity, (3) entertainment, (4) means of communication, (5) means of education, (6) sociological means